Exercise addiction levels among elite level athletes and students of sports sciences faculty - Cicioğlu, Halil İbrahim and Tekkurşun Demir, Gönül and Bulğay, Celal and Çetin, Ebru (Journal of Dependence, 2019)
Objective: The aim of this study was to evaluate the age, sport age, sex and exercise addiction levels of elite athletes and sports sciences faculty students. Method: The work group of the research consists of students who study at Gazi University Faculty of Sport Sciences during fall semester of 2018-2019 academic years and licensed sports athletes in the Athletics Federation of Turkey. Participants in the 19 to 25 years age group exercise for at least 4 days a week. "Personal Information Form" prepared by the researchers and Exercise Dependence Scale” were used as data collection tools. Results: The exercise addiction levels of the elite athletes were found to be significantly higher than the levels of sports science faculty students. There was positive directional significant difference at moderate level between the age group and sport age of the elite athletes and their level of exercise addiction. In accordance with gender, the exercise addiction scores of the male athletes were significantly higher.. Conclusion: The elite athletes were in dependent group and the students of the sports sciences faculty were in the low-risk group. According to this, it can be said that there is a strong relationship between exercise addiction and more exposure to exercise. Regular exercise and exercise at increasing intensity level over the years can increase addiction at the end of many years.